Development of Interactive Learning Media Using Genially Based on Game-Based Learning - Kuncoro, Bhakti Dwi; Wijianto; Winarno (LifeSciFi, 2025)
This study aims to develop interactive learning media using the Genially platform with a Game-Based Learning approach and to examine its feasibility and effectiveness in improving learning outcomes. This research employed a research and development method based on the Sukmadinata model, which consists of three stages: preliminary study, product development, and product testing. Data were collected through observation, interviews, questionnaires, surveys, and learning achievement tests. The research subjects included material experts and media experts for validation, 12 students of class VIII B in the limited trial, and 32 students of class VIII A in the field trial. Media feasibility was determined based on expert validation and students’ responses. The results indicate that the Genially-based learning media was rated “Very Feasible” by material experts with a score of 93 and by media experts with a score of 85. Students’ responses showed a mean score of 85.5, categorized as “Very Good.” The effectiveness analysis using N-Gain based on pretest and posttest scores yielded a value of 70.05%, indicating a “Moderately Effective” level. These findings confirm that Genially-based game-based learning media can enhance students’ engagement and learning outcomes.